N-Tupled Coincidence Point Theorems for Probabilistic ψ-Contractions in Menger Spaces. (20th March 2016) - Murthy, Penumarthy Parvateesam; Patel, Uma Devi
Abstract : We introducedn -tupled coincidence point for a pair of mapsT : X n → X andA : X → X in Menger space. Utilizing the properties of the pseudometric and the triangular norm, we will establishn -tupled coincidence point theorems under weak compatibility as well asn -tupled fixed point theorems for hybrid probabilisticψ -contractions with a gauge function. Our main results do not require the conditions of continuity and monotonicity ofψ . At the end of this paper, an example is given to support our main theorem.